Regional Healthcare Ecosystem Analyst for Healthcare Associated Infect ions - Lee, Bruce Y. (2018)
Understanding and preventing the spread of both endemic and emerging h ealthcare-associated infectious diseases throughout hospitals and nurs ing homes is a national priority. Our work has shown that the many dis parate inpatient healthcare facilities in a region can form a complex healthcare ecosystem connected by both direct and indirect patient sha ring allowing pathogens in one health care facility to readily spread to other facilities. Our goal is to further develop RHEA (Regional Hea lthcare Ecosystem Analyst) into a user-friendly software tool that dec ision makers (e.g., policy makers, funders, product developers and man ufacturers, healthcare administrators, infection prevention specialist s, researchers, and educators) can readily use to help healthcare ecos ystems prevent and control the spread of an endemic pathogen, methicil lin- resistant Staphylococcus aureus (MRSA), and an emerging pathogen, carbapenem-resistant Enterobacteriaceae (CRE). This next generation o f RHEA will bring multiple innovations by: 1) further elucidating the interconnectedness of the ecosystem and showcasing the value of cooper ation among facilities versus the current individual facility approach to infectious disease control, 2) incorporating new healthcare ecosys tem responses for endemic MRSA and emerging CRE, 3) continuing our wor k integrating economic and operational models into a framework of infe ctious disease epidemiological models, 4) imbuing virtual patients wit h characteristics linked to MRSA and CRE transmission and outcome risk , 5) building a comprehensive """"""""virtual laboratory"""""""" to he lp address many existing and future healthcare ecosystem infectious di sease questions, and 6) building a user-friendly modeling tool that de cision makers can use. The project will continue our team's longstandi ng modeling work and developing computational tools for decision maker s via three specific aims. First, completing Specific Aim 1 will expan d RHEA by adding the following capabilities: i) integrated clinical ou tcome and economic models, ii) more extensive and detailed patient cha racteristics linked to changes in infection risk and costs, iii) expan ded HAI control measures, and iv) stochastic and adaptive disease para meters to represent emerging and evolving diseases. Next, Specific Aim 2 will use our newly expanded RHEA framework to model a sample endemi c pathogen, MRSA, and a sample emerging pathogen, CRE to identify opti mal control strategies even when pathogen characteristics are evolving . Finally, Specific Aim 3 will involve developing a user-friendly inte rface for RHEA and deploying it as a healthcare ecosystem computationa l modeling tool that various stakeholders (e.g., policy makers, health care administrators, infection control specialists, funders, and produ ct manufacturers) can readily use to make decisions regarding the cont rol of healthcare-associated infections. Public Health Relevance Under standing and preventing the spread of healthcare-associated infectious diseases throughout hospitals and nursing homes is a national priorit y. Simulation models can serve as virtual laboratories to help identif y best practice solutions for containing common [such as methicillin-r esistant Staphylococcus aureus (MRSA)] and emerging [e.g., carbapenem- resistant Enterobacteriaceae (CRE)] causes of healthcare associated in fections (HAIs). Our goal is to develop our software RHEA (Regional He althcare Ecosystem Analyst) into a computational modeling tool that ca n be used directly by decision makers to identify, develop, and evalua te strategies and interventions to reduce HAIs across a large geograph ic region.